2011
DOI: 10.1021/jp207483y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Parameters on Ultrafast Hydrogen Migration in Methanol Studied by Coincidence Momentum Imaging

Abstract: The effect of intensity, duration, and polarization of ultrashort laser pulses (795 nm, 40-100 fs, and 0.15-1.5 × 10(15) W/cm(2)) on the hydrogen migration in methanol is systematically investigated using Coulomb explosion coincidence momentum imaging. The ratio of the ion yield obtained for the migration pathway CH(3)OH(2+) → CH(2)(+) + OH(2)(+) with respect to the sum of the yields obtained for the migration pathway and for the nonmigration pathway CH(3)OH(2+) → CH(3)(+) + OH(+) exhibits a small (10-20%) but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…This result is somewhat unexpected since the formation of molecular hydrogen ions and hydrogen migration channels are described in the related literature as processes competitive to multiple ionization. 3,6,26,29 In order to evaluate the relative contribution of hydrogen atoms originating from the CH 3 -or the phenyl (C 6 H 5 -) moieties we recorded the mass spectra of two deuterium labeled isotopes of toluene (C 6 D 5 CH 3 , C 6 D 5 CD 3 ) at similar irradiation conditions.…”
Section: The C 7 H 8 Casementioning
confidence: 99%
See 2 more Smart Citations
“…This result is somewhat unexpected since the formation of molecular hydrogen ions and hydrogen migration channels are described in the related literature as processes competitive to multiple ionization. 3,6,26,29 In order to evaluate the relative contribution of hydrogen atoms originating from the CH 3 -or the phenyl (C 6 H 5 -) moieties we recorded the mass spectra of two deuterium labeled isotopes of toluene (C 6 D 5 CH 3 , C 6 D 5 CD 3 ) at similar irradiation conditions.…”
Section: The C 7 H 8 Casementioning
confidence: 99%
“…3 At the same time, several researchers have attempted a step further towards the control of hydrogen migration, following different experimental techniques. [4][5][6][7] For the case of acetylene isomerization, Wells et al demonstrated an enhancement of the migration efficiency by orders of magnitude by optimizing the laser pulse characteristics. The novel experimental technique employs an adaptive control scheme, where the feedback variable is the ratio of the CH + fragments (coming from the two-body dissociation of the doubly charged acetylene: [C 2 H 2 ] 2+ → CH + + CH + ) to CH 2 + cations (formed by the dissociation of doubly charged vilyldene: [C 2 H 2 ] 2+ → CH 2 + + C + ), which are recorded in each step by VMI (velocity map imaging).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitation to higher ionic energy levels during the laser pulse, on the other hand, can be achieved by field-induced transitions [9][10][11][12] or by electron recollision [13][14][15]. In practice, a mixture of these excitation mechanisms may be at work and their relative importance may strongly depend on the laser pulse parameters, in particular, on intensity and pulse duration [16,17]. In order to extend light-field control of molecular fragmentation to larger and more complex polyatomic molecules where a variety of different dissociation pathways coexist, it is necessary to enhance our knowledge about the coupling between the fast field-induced electronic dynamics and the resulting slower nuclear motion, and about the dependence of these processes on the laser parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocarbons with their intrinsically very fast intramolecular nuclear dynamics of the light hydrogen atoms or protons, which leads to a rich restructuring dynamics, are particularly interesting and have been the object of numerous experimental studies, both using coincidence detection of the molecular fragments [1,[6][7][8]16,17,[21][22][23][24][25] and without coincidence detection [9,10,26,27].…”
Section: Introductionmentioning
confidence: 99%